The molecular characteristics of oil fractions determined from ultrasonic velocity measurements - SZACHNOWSKI, Wiesław; WIŚLICKI, Bogdan (Archives of Acoustics, 1981)
This paper presents the results of measurements of ultrasonic velocity in liquid hydrocarbon multi-fraction fuels and individual hydrocarbons, on the basis of which the Rao constants, the mean distances between the surfaces of the free molecules, the Langemann constants, and the acoustic diameters of the molecules were determined. The dependencies of the acoustic constants, the distances between the molecules and the acoustic diameters of the molecule on the density and on the molecular mass for different fractions of fuels and different individual hydrocarbons are presented. It was found that the quantities used in molecular acoustics can be used to characterize the properties of multicomponent hydrocarbon mixtures and to identify their structure. The results of the investigations confirmed the usefulness of the concept presented in this paper – the concept of the inclusion of the intermolecular interaction forces by a change in the acoustically determined intermolecular distances in a hypothetical equivalent single – component liquid.